2022
DOI: 10.3390/s22041418
|View full text |Cite
|
Sign up to set email alerts
|

Attention-Based Deep Recurrent Neural Network to Forecast the Temperature Behavior of an Electric Arc Furnace Side-Wall

Abstract: Structural health monitoring (SHM) in an electric arc furnace is performed in several ways. It depends on the kind of element or variable to monitor. For instance, the lining of these furnaces is made of refractory materials that can be worn out over time. Therefore, monitoring the temperatures on the walls and the cooling elements of the furnace is essential for correct structural monitoring. In this work, a multivariate time series temperature prediction was performed through a deep learning approach. To tak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…It is evident that the optimal approach for partitioning X into k clusters can be achieved by employing the partition strategy, which entails minimizing the correlation square sum cost function min ss(∏) in Equation (23). Given that Tr X T X is determined by the sample space, the problem of min ss(∏) is considered as an equivalent optimization problem described as max U T U=I k Tr A T X T XA (24) According to the Ky Fan theorem, when dealing with a real and symmetric matrix B = X T X with eigenvalues…”
Section: Training Optmization Of Mco-pinnmentioning
confidence: 99%
See 1 more Smart Citation
“…It is evident that the optimal approach for partitioning X into k clusters can be achieved by employing the partition strategy, which entails minimizing the correlation square sum cost function min ss(∏) in Equation (23). Given that Tr X T X is determined by the sample space, the problem of min ss(∏) is considered as an equivalent optimization problem described as max U T U=I k Tr A T X T XA (24) According to the Ky Fan theorem, when dealing with a real and symmetric matrix B = X T X with eigenvalues…”
Section: Training Optmization Of Mco-pinnmentioning
confidence: 99%
“…In recent years, the rapid advancement of machine learning has spurred research into utilizing neural network models for solving PDEs [ 21 , 22 , 23 ]. One approach is data-driven PDE solutions.…”
Section: Introductionmentioning
confidence: 99%
“…Bahdanau et al [24] showed that based on their preliminary experiments on machine translation, the two methods performed comparably. However, it is not known whether this task applies to other areas, so many scholars have made empirical comparisons, such as stock prediction [25], traffic flow prediction [26], short-term runoff prediction [27], and temperature forecast [28].…”
Section: Introductionmentioning
confidence: 99%